Analysis of the Influence of Environmental Factors on Green Trust, Green Satisfaction, and Green Perceived Quality among Wardah Cosmetic Consumers in the Special Region of Yogyakarta - Shafa Fauzan (PT SOLUSI EDUKASI BERDIKARI, 2025)
This study aims to examine the effect of the environment on green trust, green satisfaction, green perceived quality on Wardah cosmetics consumers in the Special Region of Yogyakarta. In this study, the population used is both men and women in the Special Region of Yogyakarta who will or have used Wardah cosmetic products. The number of samples is 180 respondents with criteria aged 17-60 years. The analysis technique used in this study uses Structural Equation Modeling (SEM) which is processed with AMOS 22 and data collection using a purposive sampling technique. The results of this study indicate a positive influence from the influence of environmental friendliness on green trust, green satisfaction, and green perceived quality. In addition, this study also shows the positive influence of green satisfaction and green perceived quality on green trust.